A comprehensive continuum theory of structured liquids. (13th January 2023) - Blossey, R; Podgornik, R
Abstract: We develop a comprehensive continuum model capable of treating both electrostatic and structural interactions in liquid dielectrics. Starting from a two-order parameter description in terms of charge density and polarization, we derive a field-theoretic model generalizing previous theories. Our theory explicitly includes electrostatic and structural interactions in the bulk of the liquid and allows for polarization charges within a Drude model. In particular we provide a detailed description of the boundary conditions which include the charge regulation mechanism and surface polarization, which is explained both in general terms and analyzed for an exemplary model case. Future applications of our theory to predict and validate experimental results are outlined.